Dampak Akselerasi Belanja terhadap Pertumbuhan Ekonomi - Moedy, Barkah Kolista; Ling, Mei (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2024)
As one of the components of Gross Domestic Product (GDP), government expenditure realized through government consumption is closely related to economic growth There is a tendency in the government spending pattern that indicates an accumulation in the fourth quarter; thereby, the economic benefits of government spending have not been fully experienced by society. This study examines the importance of acceleration of government spending to encourage economic growth through multiplier effect. This study examines the impact of accelerated government spending—both direct and indirect—, on government consumption and gross fixed capital formation, and then performs a simulation of GDP. The results of this study show that increase in budget allocation and acceleration of budget realization have significant positive impacts on economic growth, with capital expenditure having the greatest impact on economic growth. This research recommends the reformulation of performance indicators of budget implementation (IKPA) by considering the impact of government spending on the economy, refocusing on evaluation of budget execution, and optimization the disbursement plan as policy recommendations to accelerate government spending.